Interplay of Pathogen-Induced Defense Responses and Symbiotic Establishment in Medicago truncatula - Chen, Tao; Duan, Liujian; Zhou, Bo; Yu, Haixiang; Zhu, Hui; Cao, Yangrong; Zhang, Zhongming (Frontiers in Microbiology, 2017)
Suppression of host innate immunity appears to be required for the establishment of symbiosis between rhizobia and host plants. In this study, we established a system that included a host plant, a bacterial pathogen and a symbiotic rhizobium to study the role of innate immunity during symbiotic interactions. A pathogenic bacterium, Pseudomonas syringae pv. tomato strain DC3000 (Pst DC3000), was shown to cause chlorosis in Medicago truncatula A17. Sinorhizobium meliloti strain Sm2011 (Sm2011) and Pst DC3000 strain alone induced similar defense responses in M. truncatula. However, when co-inoculated, Sm2011 specifically suppressed the defense responses induced by Pst DC3000, such as MAPK activation and ROS production. Inoculation with Sm2011 suppressed the transcription of defense-related genes triggered by Pst DC3000 infection, including the receptor of bacterial flagellin (FLS2), pathogenesis-related protein 10 (PR10) and the transcription factor WRKY33. Interestingly, inoculation with Pst DC3000 specifically inhibited the expression of the symbiosis marker genes nodule inception (NIN) and nodulation pectate lyase (NPL) and reduced the numbers of infection threads and nodules on M. truncatula A17 roots, indicating that Pst DC3000 inhibits the establishment of symbiosis in M. truncatula. In addition, defense-related genes, such as MAPK3/6, RbohC and WRKY33, exhibited a transient increase in their expression in the early stage of symbiosis with Sm2011, but the expression dropped down to normal levels at later symbiotic stages. Our results suggest that plant innate immunity plays an antagonistic role in symbiosis by directly reducing the numbers of infection threads and nodules.